2022
DOI: 10.1532/hsf.4689
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Myxoma Resection: A Single-Center 5 Years’ Experience

Abstract: Background: There is an increasing demand for minimally invasive myxoma resection. This study aimed to investigate the safety and feasibility of minimally invasive myxoma resection. Methods: In this retrospective study, we collected information from 95 patients who underwent myxoma resection between January 2016 and December 2020. Based on the operative approach, the patients were divided into the minimally invasive myxoma resection (Mini-MR) group (N = 30) and the sternotomy myxoma resection (SMR) group (N = … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Since the first successful robotic cardiac myxoma resection performed by Murphy et al in 2005 [14], the procedure has been demonstrated as a safe and feasible method with rapid recovery, cosmetic superiority, and improved postoperative quality of life when compared to the conventional sternotomy approach [4,5,13,[15][16][17][18]. This study aims to explore the differences in clinical outcomes between robotic and thoracoscopic myxoma resection, which are not well documented in previous literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first successful robotic cardiac myxoma resection performed by Murphy et al in 2005 [14], the procedure has been demonstrated as a safe and feasible method with rapid recovery, cosmetic superiority, and improved postoperative quality of life when compared to the conventional sternotomy approach [4,5,13,[15][16][17][18]. This study aims to explore the differences in clinical outcomes between robotic and thoracoscopic myxoma resection, which are not well documented in previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…Massive allogenic blood transfusion is an independent risk factor for nosocomial pneumonia following cardiac surgeries and plays an important role in postoperative kidney injury [16]. Wei S et al [8] concluded that thoracoscopic surgeries have a lower transfusion rate than robotic surgeries (52.2% vs. 64.5%) [8].…”
Section: Discussionmentioning
confidence: 99%